The Impact of Household Poverty on Child Abuse in Indonesia - Rohadatul'aisy, Nailah; Hardiawan, Donny; Sihaloho, Estro Dariatno (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: This study utilizes the expenditure approach as a measure of poverty and incorporates household-level factors to assess their impact on psychological and physical child abuse in Indonesia.Research Objectives: This study aims to analyze the impact of household characteristics, especially variations in poverty status on the risk of child abuse in Indonesia.Research Methods: This study uses Social Defense Module of the 2020 National Socio-Economic Survey (Susenas) data and the logistic regression model.Empirical Results: The results showed that children in households living below the poverty line have the highest probability of experiencing psychological and physical abuse. Factors that also increase the likelihood of abuse are female-headed households, unemployment, low education levels, households with only boys and/or children aged 6-12 years, and living in rural areas.Implications: These findings highlight that child protection and abuse prevention policies should focus more on economic and social interventions, with poor households as the primary target.JEL Classification: D19, I31, I32, J13How to Cite:Rohadatul’aisy, N., Hardiawan, D., & Sihaloho, E. D. (2025). The Impact of Household Poverty on Child Abuse in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 131-148. https://doi.org/10.15408/sjie.v14i1.45142.